Comparison of Seed Germination, Root and Shoot Length of Maize and Wheat Crops with Compost Leachate and Commercial Fertilizer - Ameen, Ayesha; Mushtaq, Omer (BioScientific Review, 2019)
The increasing public concern about municipal solid waste (MSW) due to its impact on health and environment induces people to think about more ways of recycling this waste. These days, people strive to find more appropriate methods and processes to treat MSW for its proper management and disposal. Composting process is the most appropriate method of recycling used to get rid of organic fractions. The most important concern is the production of compost leachate. This study was designed to check the potential of compost leachate as a chemical fertilizer and to compare it with commercial fertilizer. Different dilutions of compost leachate and commercial fertilizer were used to check their effects on seed germination of wheat and maize crop and the initial root and shoot length measurement of these crops. Germination index, germination inhibition and germination rate were also evaluated in different experimental trials with variation in leachate dilution. The results showed best root, shoot length and seed germination at low quantity of leachate sample. The obtained results showed that leachate has better fertilizer qualities as compared to commercial fertilizer. Moreover, it is more economical and environment friendly. It also helps in maintaining the structure of soil and conditions the soil.